Diversity in the Ammonia-Oxidizing Nitrifier Population of a Soil - Belser, L. W. (1978)
Multiple genera of ammonia-oxidizing chemoautotrophic nitrifiers in a soil were detected, isolated, and studied by means of modified most-probable-number (MPN) techniques. The soil examined was a Waukegon silt loam treated with ammonium nitrate or sewage effluent. The genera Nitrosomonas and Nitrosospira were found to occur more commonly than the genus Nitrosolobus. Three different MPN media gave approximately the same overall ammonia oxidizer counts within statistical error after prolonged incubation but differed markedly in ratios of Nitrosomonas to Nitrosospira. Selectivity and counting efficiency of MPN media were studied by observing the growth response of representative pure cultures isolated from the soil. Selectivity was evident in each medium with respect to all strains tested, and the media differed greatly in incubation times required to obtain maximum counts.